2017
DOI: 10.1653/024.100.0243
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Behavior of Long-Legged Flies (Diptera: Dolichopodidae) and Their Potential Negative Effects on the Parasitoid Biological Control Agent of the Asian Citrus Psyllid (Hemiptera: Liviidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Crop habitats hosted the greatest abundance of Condylostylus and Chrysotus, confirming the patterns found with previous studies on the group on agroecosystems (Harterreiten-Souza et al, 2020). Both genera are assumed to be generalist predators that prey on aphids (Aphididae), whiteflies (Aleyrodidae), mites (Eriophydae), thrips (Thripidae) and small parasitoid wasps (Ulrich, 2004;Cicero et al, 2017). All these prey insects are expected to be more common in the crops than in other habitat types due to food availability (Rand et al, 2006;Tscharntke et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Crop habitats hosted the greatest abundance of Condylostylus and Chrysotus, confirming the patterns found with previous studies on the group on agroecosystems (Harterreiten-Souza et al, 2020). Both genera are assumed to be generalist predators that prey on aphids (Aphididae), whiteflies (Aleyrodidae), mites (Eriophydae), thrips (Thripidae) and small parasitoid wasps (Ulrich, 2004;Cicero et al, 2017). All these prey insects are expected to be more common in the crops than in other habitat types due to food availability (Rand et al, 2006;Tscharntke et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…For example, Michaud (2004) found that T. radiata suffer mortality (64-95%) due to predation of parasitized nymphs by lady beetles in central Florida. Also, dolichopodids compete for resources with T. radiata and eat them if encountered during normal host searching/feeding behavior (Cicero et al 2017). In our study, T. radiata rarely were observed in groves under both management regimes.…”
Section: Discussionmentioning
confidence: 49%
“…Although we did not observe spiders directly consuming D. citri, some psyllids were found ensnared within their webs. Dolichopodids, also known as predatory long-legged flies, feed on adult D. citri (Chong et al 2010;Cicero et al 2017) and were the third most frequently observed arthropods group in our study. More dolichopodids were found in intermittently sprayed than organic groves.…”
Section: Discussionmentioning
confidence: 60%
“…The family was the Diptera most abundant in coconut crops in the state of Espírito Santo, southeast Brazil (Comério & Benassi 2013). Condylostylus was the most abundant genus in Citrus orchards from Vero Beach, Florida, USA, and the individuals were observed displaying predatory activity, thus reinforcing the evidence of their natural enemy role in agroecosystems (Cicero et al 2017). Harterreiten-Souza et al (2020) demonstrated that Condylostylus species are more abundant in agricultural crops than in agroecosystems.…”
Section: Condylostylus Electus (Walker 1852)mentioning
confidence: 58%